Acute phase protein and vitamin D concentration in dogs with multicentric lymphoma - do Carmo Pereira Rocha, Michelle [UNESP]; Garnica, Taismara Kustro; Fukumasu, Heidge; Ramirez, Ricardo Andres; Pazzini, Josiane Morais; Sueiro, Felipe Augusto Ruiz; de Paiva, Felipe Noleto [UNESP]; De Nardi, Andrigo Barboza [UNESP] (FapUNIFESP (SciELO), 2022)
This study aimed to evaluate the serum concentration of vitamin D (25-Hydroxyvitamin D) and acute phase proteins (APPs; alpha- 1 acid glycoprotein, haptoglobin, transferrin, ceruloplasmin, albumin, IgA, IgG and alpha-1 - antitrypsin) as potential biomarkers for prognostic and therapy response in dogs with multicentric lymphoma submitted to the CHOP (Cyclophosphamide, Doxorubicin, Vincristine and Prednisone) chemotherapy protocol. Thirteen dogs with multicentric lymphoma classified as high grade by cytology were included in the treatment group (GL), while ten healthy dogs were included in the control group (GC). Serum was collected in the weeks T0, T5 and T10 of CHOP chemotherapy protocol, for the GL group, and in a single collection, for the GC group. All the collected samples were evaluated for the APPs and vitamin D concentrations through electrophoresis and chemiluminescence methods, respectively. Diagnostic and staging tests were performed for all the dogs in the GL group, and included cytopathology, histopathology and immunohistochemistry of the affected lymph node. Of these dogs, 9 achieved a complete response and 4 a partial response to the treatment. Data analysis was performed with the R software. The results demonstrated that serum concentrations of IgA, haptoglobin and α1-acid glycoprotein were significantly different between the groups and also between the different chemotherapy times analyzed (p<0.05), indicating that these proteins can be considered as sensitive biomarkers for lymphoma in dogs. Furthermore, the α1-acid glycoprotein showed prognostic value for the disease, with 63% specificity. However, vitamin D concentration was not correlated with prognosis of the dogs with lymphoma.
Keywords: acute phase reaction; hematopoietic neoplasia; lymphosarcoma; prognosis; therapeutic response